No place to go: statelessness in Israel - Oded Feller (Forced Migration Review, 2009)
Only in the past few years has Israel acknowledged that thereexists a problem of stateless persons living in Israel; however,this has not prompted the state to recognise the distress ofstateless people or to develop appropriate solutions.